(untitled) (Damascus University Journal for engineering sciences, 2022)
The research aims to study the phenomenon of repetition in the contemporary artistic experiments to identify the aesthetic values and its expressive dimensions , in the relationship with the design elements. The repetition is considered as an artistic phenomenon that was known in the ancient art. The artists harnessed it in their works to express their thoughts and visions. In fact, the repetition exhibits in its structure different aesthetic, plastic, expressive and psychological connotations that are imposed by the nature of the artistic state. The phenomenon of repetition is one of the most important phenomena in the contemporary and modern art works. The objectif the research is to define the aesthetics and the phenomenon of repetitions, and how they occur through a series of relationships with the elements of the painting. And how it explores its aesthetic and expressive importance and values that imposes. In addition the research aims to define the manner of its presence in the contemporary painting.